Using organic wastes as feed substrates for black soldier fly larvae - Msangi, J. W.; Mweresa, C.K.; Ndong’a, F.M. (Wegeningen Academic Publishers, 2021)
Feeding black soldier fly larvae (BSFL) on locally available organic wastes has the potential of providing an alternative source of protein to fishmeal and soybean used in animal feed formulation. This can also mitigate against increasing accumulation of organic wastes and reduce high costs associated with their disposal. This study assessed the effects of three locally available organic waste substrates namely Irish potato peels, kale remains and bovine ruminal content versus chick mash as a positive control on larval weight gain, prepupal yield, substrate reduction rate, bioconversion rate and conversion ratio of BSFL. Analysis of variance (ANOVA) was used to determine whether organic feed substrates had significant effects on BSFL while Tukey HSD, post-hoc test was applied for multiple comparisons and mean separation at P<0.05. Organic waste feed substrates influenced larval weight gain and prepupal yield (P<0.01), biomass reduction rate (P=0.04), bioconversion rate (P=0.01) and conversion ratio (P=0.04) of BSFL produced. Kale remains performed better than Irish potato peels and bovine ruminal contents implying that they can be enriched to provide an alternative feed for BSFL instead of chick mash. This study demonstrated that the three locally available organic waste substrates can be used to feed BSFL for sustainable production of animal feed. Black soldier fly larvae have the potential of providing a viable solution for degradation and disposal of ever-increasing quantities of organic wastes in the markets, towns and cities of sub-Saharan Africa.
Keywords: weight gain, yield, bioconversion, alternative protein, sustainable production